New ichnological record from the late campanian Toro Toro Formation at Toro Toro, Potosí (Bolivia): first probable dromaeosaurid tracks from South America - Apesteguía, Sebastián (2011)
Dromaeosaurids have a characteristic pes with a larger central third digit, a slightly smaller fourth one, and a second one represented by a ball-shaped pad that supported a retracted, deeply curved claw that did not come into contact with the ground (Ostrom, 1969). The group had hitherto been reported only from Late Jurassic to Cretaceous deposits in northern continents. However a substantial change in the perception of their paleobiogeographic history arose when several South American and Malagasy maniraptorans were discovered (Novas and Puerta, 1997; Forster et al., 1998; Calvo et al., 2004; Makovicky et al., 2005; Novas and Pol, 2005; Novas et al., 2008). The record of vertebrate tracks in Bolivia is one of the most important and diverse of the world (Branisa, 1968; Bonaparte at el., 1984; Leonardi, 1994; Meyer et al., 2001; Lockley et al., 2002). The aim of this paper is to describe and analyze ichnotaxonomically some tracks with peculiar features that suggest probable dromaeosaurid affinities. These tracks were found in the Toro Toro Formation (Upper Cretaceous) at Toro Toro, Potosí Department, Bolivia. Aspects of the paleobiology of the putative trackmakers are also discussed. The specimens examined –briefly mentioned by Apesteguía et al. (2007)– are tracks preserved as natural molds. The original material is still in situ, but two plaster replicas of one of the footprints were made. One of these is housed in the collection of the Félix de Azara Foundation, Buenos Aires, Argentina (CFA-PA-852), while the other is in the Toro Toro National Park headquarters, Bolivia, with no collection number.